Optimal design of maintenance service contract considering preventive maintenance, random repair cost and time value of money - Majeed Heydari; Amir Yousefli (International Journal of Research in Industrial Engineering)
Offering Maintenance Service Contracts (MSCs) for production equipment can be a good source of revenue for theProviders of these services. To do this, designing an optimal MSC with a minimum price will be of great interest to service providers. In this paper, the effect of conducting periodic preventive maintenance on the failure process of a given equipment item and its corresponding cost are studied. Assuming minimal repair at failure with a random repair cost, the expected cost of maintenance service is estimated. Due to the time delay between selling the contract and paying the repair bills, the time value of service cost at the time of selling the contract is derived. Then, the cost-plus approach is used to determine the price of the MSC. In the presented model, the service provider determines the number of preventive maintenance and the improvement level to minimize the expected price of the MSC. A numerical example with comprehensive sensitivity analysis is presented to illustrate the model and its parameters' effect. The result shows that the presented model helps the service provider to design an MSC with a minimum price while assuring the profit margin.